2019
DOI: 10.1089/jwh.2018.7020
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Diabetes and Maternal Weight Management During and After Pregnancy

Abstract: Background: Women diagnosed with gestational diabetes mellitus (GDM) substantially modify their diets during pregnancy to control hyperglycemia. These changes could also affect maternal weight management. Materials and Methods: From July 2014 to December 2015 we enrolled women with and without GDM in a prospective cohort study to compare their mean rates of (1) weight gain before GDM screening, (2) weight gain after GDM screening, and (3) postpartum weight loss. All GDM-affected women were referred to Medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
(38 reference statements)
4
8
0
2
Order By: Relevance
“…Consistent with our findings, previous studies in women with heterogeneous BMIs assessing weight gain in the interval after GDM screening have found that women without GDM gain more weight than women with GDM [12,14]. In a small US study of 89 women, Chakkalakal et al reported that women with GDM gained weight at a lower rate than women without GDM (0.30 ± 0.28 kg/week vs. 0.53 ± 0.28 kg/week, p = 0.001) [12].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Consistent with our findings, previous studies in women with heterogeneous BMIs assessing weight gain in the interval after GDM screening have found that women without GDM gain more weight than women with GDM [12,14]. In a small US study of 89 women, Chakkalakal et al reported that women with GDM gained weight at a lower rate than women without GDM (0.30 ± 0.28 kg/week vs. 0.53 ± 0.28 kg/week, p = 0.001) [12].…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our findings, previous studies in women with heterogeneous BMIs assessing weight gain in the interval after GDM screening have found that women without GDM gain more weight than women with GDM [12,14]. In a small US study of 89 women, Chakkalakal et al reported that women with GDM gained weight at a lower rate than women without GDM (0.30 ± 0.28 kg/week vs. 0.53 ± 0.28 kg/week, p = 0.001) [12]. Similarly, women with GDM gained less total weight than women without GDM in a study of 212 Australian women, when weight was assessed in the second and third trimester (GDM: 1.18 kg (1.6%) vs. non-GDM: 4.0 kg (4.8%), p < 0.001) [14].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Previous studies on the role of GWG in GDM are contradictory. 33,34 These contradictory results may be attributed to dietary regulation and exercise of pregnant women after being diagnosed with GDM. [35][36][37] In this study, many pregnant women gained more weight than that recommended by the IOM guidelines, especially for women who were overweight and obese.…”
Section: Discussionmentioning
confidence: 99%